Prescripción de corticoides en pacientes COVID-19 en 2 hospitales de Trujillo: Corticosteroid prescription in COVID-19 patients at 2 hospitals in Trujillo - Meza-Lázaro, Cecilia Ivonne (2022)
Objetive: To identify the trend of prescription of corticosteroids in two hospitals. Methods: Observational, data were collected on the prescription of corticosteroids in outpatient, emergency and hospitalization services. The  COVID-19 cases curve was matched with the percentage of monthly prescriptions, percentage distributions of the prescription of corticosteroids were made (according to form of presentation), in addition to the percentage distribution of corticosteroid prescriptions according to the amount per patient. Results: During the period from April 2020 to March 2021, 36,194 cases of covid were registered in Hospital II Florencia de Mora, registering a prescription of 7,163 corticosteroids (75.64%). In 2020, 736 patients with covid-19 were registered at the Virgen de la Puerta hospital from April to December; of these, 244 received one or more corticosteroids, with a total of 338 prescriptions. 80% of prescriptions was made between May and July. Conclusion: The prescription of corticosteroids increased during the pandemic, especially during the months of June and July 2020 and with greater use of dexamethasone.